Arquitetura situacional: investigações sobre memória e imaginação como aportes teóricos para a construção de narrativas - Diogo Ribeiro Carvalho (2011)
This dissertation begins by criticizing the current homogenization and mass production of space, due to the uncritical and uncompromising position taken by many architects, engineers and builders. In the nineteenth century, Georg Simmel identified the development of ageneralized condition of apathy, passivity and an anesthesia of persons with respect to living space. Such urban pathology worsens throughout the twentieth century, especially through the dissemination of modernist design method, a simplistic model of predeterminations, andthe ongoing reduction of architecture to a mere commodity governed by the economies and markets. We propose the construction of other possibilities for architectural practices, which serve to resist this state of affairs. An architecture concurrently contextual and self-reflective,that is, one that recognizes the idiosyncrasies of each situation and is critical of its own production. For the development of this notion of architecture that is intended to be critical and creative, the investigations made cross distinct contemporary architectural practices, yetcomplementary to each other the artificial excavations of Peter Eisenman; the palimpsests and intertextualities of Daniel Libeskind; Louis Kahns archetypes; the critical regionalism of Kenneth Frampton, Liane Lefaivre and Alexander Tzonis; Bernard Tschumis kinematics; thearchitecture of the feeling of Juhani Pallasma; the idiosyncratic architecture of Enric Miralles, and the ambiguous spaces of Nannette Jackowski and Ricardo de Ostos with theories of memory and imagination the enlargement of perception proposed by Henri Bergson, the notions of collective memory of Maurice Halbwachs, Pierre Nora, John Frow, Andreas Huyssen and Paul Ricoeur, the ethical and poetical imagination developed by Richard Kearney. The aesthetic categories of the sublime and of the magical realism support the construction of sucha situational architecture, founded on the recognition of the emergence to think architecture within structures of otherness.